SEX EDUCATION FOR SMART POPULATION: A Fundamental Mechanism in Enriching Human Security and Reduction Poverty - Fivi Elvira (STAIN MAJENE, 2023)
Poverty and human security are domestic problems that occur in many countries. This caused by the population continuing to increase and not being optimal in suppressing the population which increase every minute. Sex education is one of the solutions to reduce the population and explain that premarital sexual behavior continues to increase from year to year. For instance, the emergence of unwanted pregnancies, abortions, dropping out of school, and contracting non-communicable diseases. This study aims to examine the sex education for smart population to enriching human security and reduction the poverty. Due to the fact that such education would seek to empower people to make the right decisions with correct information on anatomy, contraception, and disease identification and prevention. The intended effects of the intervention include prevention of unintended births, prevention of AIDs and sexually transmitted diseases, and the prevention of overpopulation which can cause hunger and it will happen eventually in malnutrition everywhere.